Role of transarterial chemoembolization for hepatocellular carcinoma with extrahepatic metastases in the era of advancing systemic therapy - Byeong Geun Song; Myung Ji Goh; Wonseok Kang; Dong Hyun Sinn; Geum-Youn Gwak; Yong-Han Paik; Joon Hyeok Lee; Moon Seok Choi (Korean Liver Cancer Association, 2024)
Backgrounds/Aims Systemic therapy is the current standard treatment for hepatocellular carcinoma (HCC) with extrahepatic metastasis (EHM). However, some patients with HCC and EHM undergo transarterial chemoembolization (TACE) to manage intrahepatic tumors. Herein, we aimed to explore the appropriateness of TACE in patients with HCC and EHM in an era of advanced systemic therapy. Methods This study analyzed 248 consecutive patients with HCC and EHM (median age, 58.5 years; male, 83.5%; Child-Pugh A, 88.7%) who received TACE or systemic therapy (83 sorafenib, 49 lenvatinib, 28 immunotherapy-based) between January 2018 and January 2021. Results Among the patients, 196 deaths were recorded during a median follow-up of 8.9 months. Patients who received systemic therapy had a higher albumin-bilirubin grade, elevated tumor markers, an increased number of intrahepatic tumors, larger-sized tumors, and more frequent portal vein invasion than those who underwent TACE. TACE was associated with longer median overall survival (OS) than sorafenib (15.1 vs. 4.7 months; 95% confidence interval [CI], 11.1-22.2 vs. 3.7-7.3; hazard ratio [HR], 1.97; P<0.001). After adjustment for potential confounders, TACE was associated with statistically similar survival outcomes to those of lenvatinib (median OS, 8.0 months; 95% CI, 6.5-11.0; HR, 1.21; P=0.411) and immunotherapies (median OS, 14.3 months; 95% CI, 9.5-27.0; HR, 1.01; P=0.973), demonstrating survival benefits equivalent to these treatments. Conclusions In patients with HCC and EHM, TACE can provide a survival benefit comparable to that of newer systemic therapies. Accordingly, TACE remains a valuable option in this era of new systemic therapies.